Residental landscape: the natural environment of the Late Bronze settlements in the Tobol region - Ryabogina N.E.; Ivanov S.N.; Nasonova E.D. (Вестник археологии, антропологии и этнографии, 2018)
This article addresses one of the most important issues in landscape archaeology, i.e. the landscape prefe-rences of ancient populations depending on the patterns of nature management that these peopled used. Since forest-steppe regions are characterized by a mosaic plant cover, the appearance of residential landscapes — the natural environment around ancient settlements — can be restored using paleo-economic population models. This work is aimed at analysing the characteristics of residential landscapes in the late Bronze Age on the example of three settlements in the Tobol region (south of Western Siberia), which were inhabited by the representatives of the Fedorovо, Pakhomovо and Cherkaskul cultures. To this end, the blocks of palynological data obtained from different archaeological contexts were compared with each other, well as with the background natural conditions reconstructed for the south of Western Siberia. The paper presents the detailed analysis of both pollen data and non-pollen palynomorphs collected from the soil sediments of the cultural layers, as well as the results of the natural environment reconstruction. The cultural layer of the Fedorovо settlement (Bochantsevo 1, up to the 16th century BC) is shown to contain predominantly meadow pollen, typical weeds of human habitats and the spores of coprophilous fungi. The residential landscape of this village consisted in an open place with meadow grass vegetation, without signs of steppe, with small birch forests nearby. A similar situation was reconstructed for the settlement of Cherkaskul culture (Khripunovskoe 1, 16–13th century BC); here, the household economy was based on the breeding of cattle, with people preferring to settle open forest-steppe areas. On the basis of pollen data analysis, a completely different residential landscape was reconstructed for the Pakhomov culture settlement (Zavodoukovsk 11, 13–11th century BC). This settlement was founded and functioned in the birch forest. Its inhabitants practiced not only cattle breeding, but also hunting and fishing. Numerous studies conducted on mixed Cherkaskul-Pakhomovo settlements across the territory of the Tobol region have allowed archaeologists to suggest the co-existence of these population groups in the same territory. Our findings show that these populations might have used different land zones within the same territory, since they chose different types of residential landscape. Differences in the economic types of these groups are likely to have influenced their landscape preferences: the Pakhomov settlements were confined to the valley birch forests, while the Cherkaskul settlements were initially localized in open spaces surrounded by lands suitable for grazing.